STUDI TENTANG GANGUAN GINJAL DAN SISTEM EKSRESI PADA MASYARAKAT DI DAERAH PESISIR - Dina Selviana; Fadhila Azzahra; Firda Khoirina; Nisrina Febria Efiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the incidence of kidney disorders and excretory system problems in coastal communities, as well as the factors influencing them. Kidney disorders are a significant health issue that can seriously affect the quality of life, especially in areas with limited access to clean water and healthcare services. Coastal areas often face environmental challenges such as high salt content in water, inadequate sanitation, and lifestyles that are not fully supportive of health. This research uses a case study approach focusing on several residents experiencing kidney problems. The results indicate a significant correlation between the quality of drinking water and the frequency of complaints related to the excretory system, such as pain during urination, swelling in certain body parts, and chronic fatigue. Additionally, the low level of public awareness regarding kidney function and disease prevention also emerges as a risk factor exacerbating the condition. The study recommends the need for ongoing health education, improved access to clean water, and routine health screenings for coastal communities. With preventive and promotive efforts, it is hoped that the incidence of kidney disorders will decrease, thereby improving the well-being of the coastal communities.